(untitled) (Global Business Management Review (GBMR), 2022)
Parties conducting electronic businesses usually do not meet face-to-face, nor do they exchange currency or hard copies of documents hand-to-hand. When companies enter electronic commerce transactions, choosing an electronic payment (or E-Wallet) system that will work well is a major issue. In the present study, initially, after examining different E-Wallet systems in the Klang Valley, Malaysia, assessment criteria were identified based on previous research and experts interviews. The assessment criteria were used for questionnaire development to rank factors for selection of the best E-Wallet in the Klang Valley, Malaysia. The survey result was analyzed using the analytic hierarchy process (AHP), a mathematical model, and synthesized using Superdecisions® software. Then, applying the AHP, the five top E-Wallets used in the Klang Valley were ranked. Results show that Samsung Pay is the most preferred E-Wallet system, followed by Lazada Wallet and Boost. The findings of this research are intended to be useful for both academic researchers and companies planning to adopt or improve their electronic payment systems. The hierarchical model developed in this study is expected to provide valuable guidance to E-Wallet service providers, banking industry practitioners, financial institutions, and similar companies in optimizing their resources. E-Wallet service providers can use the results to increase the adoption of their E-Wallet transactions.